2001
DOI: 10.1002/1097-4636(2001)58:1<97::aid-jbm140>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-sterilizing and self-cleaning of silicone catheters coated with TiO2 photocatalyst thin films: A preclinical work

Abstract: TiO(2) photocatalysts were successfully coated on silicone catheters or medical tubes by pretreatment of the silicone surface with a sulfuric acid solution (5 M) for 3 h. The TiO(2) film adhered to the silicone substrate strongly against tensile and bending stresses. On the TiO(2)-coated silicone-catheters under UV illumination, both the bleaching of methylene blue dye and the photocatalytic bactericidal effect on Escherichia coli (E. coli) cells were confirmed. Thus, this type of catheter can be sterilized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(91 citation statements)
references
References 17 publications
1
86
1
3
Order By: Relevance
“…Ohko et al [25] reported that the TiO 2 photocatalyst was successfully used as a coating in silicon catheters and medical tubes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohko et al [25] reported that the TiO 2 photocatalyst was successfully used as a coating in silicon catheters and medical tubes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…An alternative to the existing methods is application of antimicrobial agents based on nanoparticles of different metals and oxides. Thus, silver, copper and titanium dioxide (titania) nanoparticles are widely used and they show strong biocidal effects on many pathogenic bacteria [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] TiO 2 has been extensively used in the development of these materials due to photocatalytic activity stimulated by ultraviolet (UV) light exposure. Upon excitation with UV light, TiO 2 generates reactive oxygen species (ROS) in the presence of water.…”
Section: Introductionmentioning
confidence: 99%
“…Ohko et al (2001) have found that silicone catheters coated with a thin layer of TiO 2 can be decontaminated using UV radiation of low intensity. Similar bactericidal effects were also observed in experiments on the sterilization of contaminated dental implants coated with titanium dioxide (Suketa et al 2005).…”
Section: Discussionmentioning
confidence: 99%